Prognostic values of preoperative albumin to globulin ratio for predicting clinical outcome in patients with high-grade gliomas - Liu, Jun; Zhan, Yun-Bo; Zhang, Feng-Jiang; Yu, Bin; Duan, Wen-Chao; Wang, Wei-Wei; Wang, Li; Yang, Bo; Zhang, Zhen-Yu (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Gliomas was the most common primary central nervous system tumors which have an increased morbidity in recent years. And the clinical prognosis of high-grade gliomas (HGG, WHO grade III to IV) was most with an average survival rate of only dozens of months. Many researchers concluded that the level of preoperative albumin-to-globulin ratio (AGR) could predict the clinical outcome of patients with solid malignant tumors. Methods: Two hundred and thirty-two cases of patients who were diagnosed HGG by pathology were enrolled in the study. The relevant data of the cohort included sex, age, preoperative Karnofsky performance score (KPS), extent of resection, albumin count and globulin count, isocitrate dehydrogenase (IDH) and survival time were collected. The survival rate was obtained by using the Kaplan-Meier method. The cut-off value of AGR was determined by X-tile software. Univariate survival analysis was performed by the log-rank method. Proportional hazards model (Cox model) was performed for multivariate analysis. Results: The optimal cut-off value of AGR was 1.32. Results showed that the preoperative AGR was correlated with clinical prognosis of patients with HGG, and the survival time of the patients with high AGR (AGR >1.32) was significantly longer. Moreover, the prognosis of patients with high AGR was better in IDH wild-type HGG. Conclusions: Preoperative AGR might predict the clinical prognosis of patients with HGG.